Objective evaluation of gait abnormalities in dogs with a thoracolumbar myelopathy using a pressure-sensing walkway - Straß, Léonie; Meller, Sebastian; Twele, Friederike; Volk, Holger A. (Frontiers in Veterinary Science, 2026)
Objective gait assessment remains essential for evaluating ambulatory function in dogs with spinal cord injury, as subjective scales depend on training and examiner experience, limiting their sensitivity to subtle changes. A rapid, standardised, and objective method is therefore needed to assess gait abnormalities and to monitor recovery over time. This study evaluates the use of a pressure-sensing walkway to objectively quantify gait characteristics in dogs with thoracolumbar myelopathy compared to healthy controls. By analysing spatio-temporal and kinetic parameters, key differences relevant to clinical monitoring were identified. Significant differences in standard deviation values were observed between controls and dogs affected by thoracolumbar myelopathy for step/stride ratio, stance phase and swing phase. Furthermore, the coefficient of variation (CV) also differed significantly between groups for step/stride ratio, stance and swing phase. CV, a marker for ataxia, was increased not only in the pelvic but also in the thoracic limbs. Lateral skewness, thoracic limb force distribution, and pelvic limb symmetry index also differed significantly between groups, with neurologically affected dogs exhibiting higher values across all parameters. In addition, a negative correlation between the Texas Spinal Cord Injury Score and the CV was identified, indicating that the CV may contribute to an objective quantification of impairment. These findings support the use of pressure-sensing walkways as a feasible and informative modality for the standardised assessment of canine patients with thoracolumbar myelopathy.